2011
DOI: 10.1002/app.35279
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of clay‐dispersed poly(styrene‐co‐methyl methacrylate) nanocomposite via miniemulsion atom transfer radical polymerization: A reverse approach

Abstract: Poly(styrene-co-methyl methacrylate) nanocomposites were synthesized using reverse atom transfer radical polymerization (RATRP) in miniemulsion. Cetyltrimethylammonium bromide (CTAB) as a cationic surfactant applicable at higher temperatures was used for miniemulsion stabilization. Successful RATRP was carried out by using 4,4 0 -dinonyl-2,2 0 -bipyridine (dNbPy) as ligand. Monodispersed droplets and particles with sizes in the range of 200 nm were revealed by dynamic light scattering (DLS). Conversion and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Although Brij98 is a common and popular surfactant in aqueous dispersed media, Simms et al demonstrated that Brij98 as a non-ionic surfactant can not effectively stabilize the miniemulsion system at high temperatures. Meanwhile, CTAB as a cationic surfactant is capable to effectively stabilize the miniemulsion system at high temperatures [41][42][43]. Therefore, by appropriate selection of ligand and surfactant successful SR&NI ATRP in miniemulsion can be achieved.…”
Section: Resultsmentioning
confidence: 98%
“…Although Brij98 is a common and popular surfactant in aqueous dispersed media, Simms et al demonstrated that Brij98 as a non-ionic surfactant can not effectively stabilize the miniemulsion system at high temperatures. Meanwhile, CTAB as a cationic surfactant is capable to effectively stabilize the miniemulsion system at high temperatures [41][42][43]. Therefore, by appropriate selection of ligand and surfactant successful SR&NI ATRP in miniemulsion can be achieved.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, Costela et al [42] have applied polymer-filled nanoporous silica aerogel as hosts for highly stable solid-state dye lasers. In addition, different initiation techniques of ATRP such as reverse atom transfer radical polymerization (RATRP) and activators generated by electron transfer ATRP (AGET ATRP) for random copolymerization of styrene and methyl methacrylate in the presence of clay nanoplatelets (dispersion approach) have been previously studied [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…7,48 Physical interaction between polystyrene chains and one surface of MCM-41 nanoparticles and finally degradation from outer surface inward can be considered as an important factor for increasing thermal stability of the nanocomposites. 33 Table 4 summarizes the extracted data from TGA and DTG curves.…”
Section: Resultsmentioning
confidence: 99%